Perceptions About HIV and Condoms and Consistent Condom Use Among Male Clients of Commercial Sex Workers in the Philippines. (April 2013) - Regan, Rotrease; Morisky, Donald E.
Because consistent condom use is an effective strategy in the prevention of sexually transmitted infections and HIV transmission, it is important to examine social cognitive influences of consistent condom use not only among female sex workers (FSWs) but also among their male clients, for whom less is known. Because little is known about how HIV knowledge and condom attitudes affect condom use among male clients of FSWs in the Philippines, the main objective was to determine what characteristics (age, education, HIV knowledge, marital status) as well as attributes taken from protection motivation theory (perceived vulnerability, perceived severity, response efficacy) are significantly associated with consistent condom use among male clients of FSWs. Logistic regression analyses showed that the odds of using condoms consistently with an FSW are 13% higher for those with more years of education (adjusted odds ratio [AOR] = 1.13; 95% confidence interval [CI] = 1.03, 1.23), higher versus lower perception of severity of HIV/AIDS (AOR = 1.97; 95% CI = 1.04, 3.73), and had a higher score for response efficacy of condoms (AOR = 1.14; 95% CI = 1.03, 1.27). Future HIV/AIDS prevention interventions that address condom use among male clients should promote educational attainment and focus on awareness of the enduring negative health consequences of acquiring HIV/AIDS, as well as cultivate positive attitudes toward the efficacy of condom use, using creative social marketing strategies.